Comparison of Electrospray Ionization and Atmospheric Chemical Ionization Coupled with the Liquid Chromatography-Tandem Mass Spectrometry for the Analysis of Cholesteryl Esters - Hae-Rim Lee; Sunil Kochhar; Soon-Mi Shim (International Journal of Analytical Chemistry)
The approach of two different ionization techniques including electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) was tested for the analysis of cholesteryl esters (CEs). The retention time (RT), signal intensity, protonated ion, and product ion of CEs were compared between ESI and APCI. RT of CEs from both ionizations decreased with increasing double bonds, while it increased with longer carbon chain length. The ESI process generated strong signal intensity of precursor ions corresponding to [M+Na]+ and [M+NH4]+ regardless of the number of carbon chains and double bonds in CEs. On the other hand, the APCI process produced a protonated ion of CEs [M+H]+ with a weak signal intensity, and it is selectively sensitive to detect precursor ions of CEs with unsaturated fatty acids. The ESI technique proved to be effective in ionizing more kinds of CEs than the APCI technique.